2016
DOI: 10.1155/2016/9384541
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability Investigation in a Reactive Sphere of Combustible Material

Abstract: An investigation of thermal stability in a stockpile of combustible material is considered. The combustible material is any carbon containing material that can react with oxygen trapped in a stockpile due to exothermic chemical reaction. The complicated process is modelled in a sphere and one-dimensional energy equation is used to solve the problem. The semi-implicit finite difference method (FDM) is applied to tackle the nonlinear differential equation governing the problem. Graphical solutions are displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Some mathematical models that are less expensive and faster than experimental approaches have been implemented in the literature to explain the auto-ignition of combustible materials in a stockpile. For instance, a one-step combustion process of heat transfer in a spherical channel was investigated in [12,13]. According to their reports, the system maintains stability as heat escapes into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mathematical models that are less expensive and faster than experimental approaches have been implemented in the literature to explain the auto-ignition of combustible materials in a stockpile. For instance, a one-step combustion process of heat transfer in a spherical channel was investigated in [12,13]. According to their reports, the system maintains stability as heat escapes into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the reviewed literature in [12][13][14]22,28], this study focuses on an investigation of the thermal decomposition of Carreau fluid in a rectangular stockpile with variable thermophysical properties. It is believed that this present study has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The continued accumulation of heat in the system, makes the temperature to raise exponentially following the Arrhenius rate law (Taghikhani, 2011;Logan, 1982). Physical parameters or factors that affect self-ignition in stockpiles of combustible materials are, among others, the material particle size, the temperature of the environment, the humidity of the material, the porosity and airflow rate of the stockpile (Lebelo, 2016;Schmidt et al, 2003). The parameters listed above need experimentation to study their influence on the temperature gradients during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of stockpiles that spontaneously combust include those of coal, hay and wood. One of the previous studies indicated that some of the veld fires are caused by spontaneous combustion of stockpiles of reactive materials, such as the dumped rubbish in the open veld [1]. A reactive material is one that contains carbon or hydrocarbon component that readily reacts with the oxygen trapped within the stockpile, due to low-temperature oxidation reaction, also called the exothermic chemical reaction [2,3].…”
Section: Introductionmentioning
confidence: 99%